Non-cutaneous soft tissue tumors and pseudotumors in the foot and ankle reported in Brazilian services - Bochi, Gabriela Silva; Ruela, Victor Hugo Morais; Souza Junior , Eli Àvila (Journal of the Foot & Ankle, 2024)
Objectives: Review the histological types of non-cutaneous soft tissue tumors and pseudotumors that affect the foot and ankle, reported in Brazilian health services. Methods: An integrative review of the literature from the Scielo and PubMed platforms, based on the descriptors “Soft Tissue Tumors,” “Pseudotumors,” “Foot, “Ankle,” and “Brazil.” Those who answered the following research question: “What are the non-cutaneous soft tissue tumors and pseudotumors in the foot and ankle reported in Brazilian health services?” were included. The combination of each author’s analysis contributed to reducing possible biases. Results: Six articles were selected, yielding 23 reports of tumors and pseudotumors, which were subsequently categorized into malignant and benign tumors. There were five benign findings: three benign tumors, two giant cell tumors, one fibromatosis, and two pseudotumors classified as synovial chondromatosis. Eighteen malignant findings were reported: seven unspecified soft tissue sarcomas, four synovial sarcomas, three myxofibrosarcomas, one fibrosarcoma, one liposarcoma, one undifferentiated pleomorphic sarcoma and one papillary intralymphatic angioendothelioma. Conclusion: In the last ten years, more reports of malignant than benign tumors have been reported. However, this finding does not necessarily reflect the Brazilian epidemiological reality, as it may represent a view in which resected benign tumors and pseudotumors are often not sent for anatomopathological study or reported in the literature. Level of evidence I; Prognostic studies - investigating the effect of a patient characteristic on the outcome of disease